An understanting of mirrors and mirroring in a schizophrenic patient obsessed with his appearance - Zworestine, Barry John (Rhodes University, Faculty of Humanities, Department of Psychology)
This work addresses the role of mirroring and mirrors encountered while working with a patient obsessed with his appearance. At the same time, however, it also attempts to provide an understanding of the process of mirroring from the developing unborn child to the adult. It examines the womb as a reflective space, the mirroring role of the mother, psychological work as mirror work, the psychopathologies of disruptive mirroring and the nature of reflection as a story, confusion and a ghostly other, and finally, the relationship between mirror reflection and psychological life. What is examined and described in this process applies not only to the specific case in study but is relevant at a universal level to all of mankind regardless of race or religion. The case-study method was used to examine the process of therapy that took place over three months. The patient's identifying data, reasons for referral, presenting problem, family background, basic personality, interpersonal relationships, mental state, diagnosis, dynamic formulation and rationale for psychotherapy were covered in detail. The process of psychotherapy over 27 sessions was recounted and discussed in detail. Theoretical understandings drawn on to facilitate an understanding of the case were from Davis and Walbridge on Winnicolt, Winnicot, Liedloff, Kay, Romanyshyn, Bettelheim, Schwartz and others.
Keywords: Schizophrenia -- Case studies; Schizophrenics -- Case studies; Mirroring; Mirrors -- Psychological aspects; Physical appearance